Protein carbonylation, cellular dysfunction, and disease progression - Dalle-Donne, Isabella (John Wiley & Sons, Ltd, 2006)
Carbonylation of proteins is an irreversible oxidative damage, often leading to a loss of protein function, which is considered a widespread indicator of severe oxidative damage and disease-derived protein dysfunction. Whereas moderately carbonylated proteins are degraded by the proteasomal system, heavily carbonylated proteins tend to form high-molecular-weight aggregates that are resistant to degradation and accumulate as damaged or unfolded proteins. Such aggregates of carbonylated proteins can inhibit proteasome activity. A large number of neurodegenerative diseases are directly associated with the accumulation of proteolysis-resistant aggregates of carbonylated proteins in tissues. Identification of specific carbonylated protein(s) functionally impaired and development of selective carbonyl blockers should lead to the definitive assessment of the causative, correlative or consequential role of protein carbonylation in disease onset and/or progression, possibly providing new therapeutic aproaches.